Studies on the induction of pregnancy and the number of fetuses during pregnancy in rats - Seung-Hee Choi; Yong-Seong Cho; Min-Ji Kim; Chae-Hyeok Lee; Hwan-Hoo Seong; Soon-Hwa Baek; Jang-Hee Lee (The Korean Society of Animal Reproduction and Biotechnology, 2020)
This study used adult wistar-based rats to observe the sexual cycle as a morphological characteristic of vaginal epithelial cells by vaginal smearing, and investigated the fetal number through mating with male rats of the same strain. The target animal was a 12 to 13-week-old Wistar-based mature unlighted rat (weight 220 g to 240 g), room temperature 23 ± 2℃, 14 hours artificial lighting (05:00 to 19:00 hours), 10 hours Adapted individuals were used for rearing for at least 2 weeks under the conditions of the darkroom (19:00 to 05:00). The feed was managed for free feeding of pellet feed for animals and water. The vaginal smearing method was used for the experiments by observing the sexual cycle every morning and confirming that the normal sexual cycle of 4 or 5 days was repeated at least 2 cycles or more. As a result, the proestrus was found to have few red blood cells, the cells and nuclei were rather large and round, and many nucleated cells were identified. In the case of the estrus, the cells were large and the nuclei were not stained, and most of the keratinocytes were found. In addition, in the metestrus and diestrus, there were many white blood cells, and it was confirmed that nucleated epithelial cells and keratinocytes were significantly reduced. The pregnancy period was 21 ± 1.8 days, and the number of live births per delivery was 11.9 on average. The number of fetuses on the 8th and 10th days of pregnancy were 15.2 ± 0.4 and 15.4 ± 0.3, respectively. On the contrary, the number of fetuses on the 12th day of pregnancy was 12.9 ± 0.6, which was significantly (p < 0.05) decreased compared to the 10th day of pregnancy, and the number of fetuses was similar until delivery. As a result of investigating the change of body weight according to the birth weight and growth stage after delivery, the birth weight of female and male was 9.2 ± 2.0 g and 9.8 ± 2.5 g, respectively. After that, until the 16th day, the female and the male showed similarly moderate weight gain, and then showed a rapid weight gain until the 21st day of lactation. With reference to the results of this study, it is expected to be used as basic data for determining the mating time of rodents and controlling pregnancy and fetal number.